2006
DOI: 10.1016/j.cmet.2006.05.011
|View full text |Cite|
|
Sign up to set email alerts
|

Oxidative metabolism and PGC-1β attenuate macrophage-mediated inflammation

Abstract: Complex interplay between T helper (Th) cells and macrophages contributes to the formation and progression of atherosclerotic plaques. While Th1 cytokines promote inflammatory activation of lesion macrophages, Th2 cytokines attenuate macrophage-mediated inflammation and enhance their repair functions. In spite of its biologic importance, the biochemical and molecular basis of how Th2 cytokines promote maturation of anti-inflammatory macrophages is not understood. We show here that in response to interleukin-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
1,007
4
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,156 publications
(1,059 citation statements)
references
References 43 publications
40
1,007
4
8
Order By: Relevance
“…Vats and colleagues highlighted the importance of mitochondrial oxidative phosphorylation in the induction of M2-type macrophages through IL-4 signaling. They observed that mitochondrial inhibition in macrophages blocked the antiinflammatory effects of IL-4 (30). In the present study, addition of the mitochondrial inhibitor oligomycin prevented the suppression of TNF-a and the enhancement of phagocytosis in macrophages by MSC CM, demonstrating that the MSCs' effect is critically dependent on oxidative phosphorylation ( Figures 6A and 6B).…”
Section: Original Articlementioning
confidence: 49%
See 1 more Smart Citation
“…Vats and colleagues highlighted the importance of mitochondrial oxidative phosphorylation in the induction of M2-type macrophages through IL-4 signaling. They observed that mitochondrial inhibition in macrophages blocked the antiinflammatory effects of IL-4 (30). In the present study, addition of the mitochondrial inhibitor oligomycin prevented the suppression of TNF-a and the enhancement of phagocytosis in macrophages by MSC CM, demonstrating that the MSCs' effect is critically dependent on oxidative phosphorylation ( Figures 6A and 6B).…”
Section: Original Articlementioning
confidence: 49%
“…The influence of mitochondrial transfer on macrophage phenotype, however, has not been studied extensively. Vats and colleagues showed the importance of mitochondrial oxidative phosphorylation in the induction of IL-4-induced antiinflammatory M2 macrophage polarization (30). Indeed, glucose metabolism is intrinsically linked to a macrophage activation state with M1 proinflammatory macrophages using glycolysis (31).…”
mentioning
confidence: 99%
“…On the other hand, M2 macrophages are scattered in interstitial spaces between adipocytes [20]. It is known that M1 macrophages are induced by proinflammatory mediators such as lipopolysaccharide (LPS) and Th1 cytokine interferon-γ (IFN-γ), whereas M2 macrophages are polarized by the stimulation with Th2 cytokines such as interleukin-4 (IL-4) and IL-13 [19,22]. Recent studies have also shown that epigenetic changes and noncoding RNAs are involved in macrophage polarization [23,24].…”
Section: Heterogeneity Of Adipose Tissue Macrophagesmentioning
confidence: 99%
“…TLR4-deficiency protects against obesity-induced adipose tissue inflammation without affecting body weight gain. On the other hand, M2 macrophages are polarized by stimulation with Th2 cytokines such as interleukin-4 (IL-4) and peroxisome proliferator-activated receptors (PPARδ and PPARγ) [31][32][33]38) . Deficiency of PPARδ or PPARγ, specifically in macrophages, exacerbates obesity-induced adipose tissue inflammation and glucose intolerance.…”
Section: Obesity and Adipose Tissue Macrophagesmentioning
confidence: 99%